(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Peptic ulcer disease is widespread worldwide, accounting for 10-15% of all gastrointestinal diseases. Gastric and duodenal ulcers are among the most common diseases, affecting 7-10% of the adult population. This literature review discusses current views on the pathogenesis of gastric and duodenal ulcers, including the role of Helicobacter pylori infection, in patients of various age groups. The pathogenetic characteristics and clinical and morphological manifestations of peptic ulcer disease in young and elderly individuals are examined in detail.